Quality of life in studies with patients under treatment for substance abuse and addiction - Selva Rios Campêlo; Maria Alves Barbosa; Celmo Celeno Porto (Universidade Federal de Goias, 2015)
The purpose of this study was to find Quality of Life (QoL) instruments and their purpose in studies with patients under treatment for substance abuse and addiction. This is an integrative review, whose articles were available on the Virtual Health Library (VHL) and published between 2010 and 2015 with the associated descriptors "Substance-Related Disorders" and "Quality of Life". Twenty-nine texts were analyzed and the instruments were grouped into four possible uses of measurement of Quality of Life. The majority used generic instruments such as WHOQOL-Bref for general Quality of Life and the SF-36 of Health-Related Quality of Life (HRQoL). It is recommended that further studies be carried out on the use of Quality of Life instruments in relation to addiction, especially with specific instruments that are beginning to appear in some studies and which have not been consolidated in the field.